Focal Adhesion Kinase Knockdown in Carcinoma‐Associated Fibroblasts Inhibits Oral Squamous Cell Carcinoma Metastasis via Downregulating MCP‐1/CCL2 Expression. Issue 2 (9th September 2014) - Min, Anjie; Zhu, Chao; Wang, Jingyi; Peng, Shuping; Shuai, Cijun; Gao, Shan; Tang, Zhangui; Su, Tong
ABSTRACT Carcinoma‐associated fibroblasts (CAFs) have been demonstrated to play an important role in the occurrence and development of oral squamous cell carcinoma (OSCC). The aim of this study is to investigate the influence of CAFs on OSCC cells and to explore the role of focal adhesion kinase (FAK) in this process. The results showed that oral CAFs expressed a higher level of FAK than normal human gingival fibroblasts (HGFs), and the conditioned medium (CM) of CAFs could induce the invasion and migration of SCC‐25, one oral squamous carcinoma cell line. However, knockdown of FAK by small interfering RNA (siRNA) resulted in inhibition of CAF–CM induced cell invasion and migration in SCC‐25, probably by reducing the production of monocyte chemoattractant protein‐1 (MCP‐1/CCL2), one of downstream target chemokines. Therefore, our findings indicated that targeting FAK in CAFs might be a promising strategy for the treatment of OSCC in the future.